Smartphone Dependence and Academic Stress: A Psychological Analysis Among College Students - Shoira Karimova; Khurshida Nuritdinova; Nailya Sabitova; Irada Babayeva; Sardor Sabirov; Nasiba Hakimova; Bakhtijon Isroilova (International Journal of Engineering, Science and Information Technology, 2025)
The General Stress Theory (GST) posits that stress results in many inappropriate actions. This research examined the correlation between Perceived Stress (PS) and dependence on Smartphones (SP). The study posited that this correlation is mediated by Diminished Self-Control (SC) and the first pathway of the mediating factor, which is influenced by safety. A survey was conducted using cluster sampling techniques on 400 undergraduates at an educational institution in Uzbekistan. The pupils were administered the Smartphone Addicted Scale-Short Variant (SAS-SV), the Depressive Anxiety Stress Score (DASS), the SC Scale (SCS), and the Safety Questionnaire (SQ) throughout scheduled class periods. The statistical program facilitated qualitative statistics and Pearson correlation evaluations. At the same time, the research was employed to examine the mediating impact of SC and the regulating influence of safety. The mediation study indicated that, as anticipated, PS correlated with less SC, which correlated with an increased risk of dependence on SP. As expected, moderated mediation analysis revealed that the relationship between PS and SC was influenced by security. The correlation between felt anxiety and SC was more pronounced in conditions of poor security. This research offers valuable insights into the relationship between PS and the heightened risk of dependence on SP. The findings align with the GST and suggest that tangible strategies are necessary for the avoidance and treatment of addiction to SP among undergraduates.